Systematic reviews of health economic evaluations: A structured analysis of characteristics and methods applied. (4th March 2019) - Luhnen, Miriam; Prediger, Barbara; Neugebauer, Edmund A.M.; Mathes, Tim
Abstract : Introduction: The number of systematic reviews of health economic evaluations (SR‐HEs) is increasing. We aimed at providing a detailed overview of the characteristics and applied methods in recently published SR‐HEs. Methods: We searched MEDLINE (03/2017) for SR‐HEs published since 2015 using validated search filters. We included studies that performed a systematic review of full economic evaluations and searched at least one electronic database. We extracted data in a standardized, beforehand piloted form that was deduced from the items of the PRISMA and CHEERS checklists. Data were extracted by one reviewer, and a 10% random sample was verified by a second. We prepared descriptive statistical measures to describe the SR‐HEs. Results: We included 202 SR‐HEs. We identified similarities especially in the methods for information retrieval. Study selection, data extraction, and assessment of quality and transferability were frequently not reported or performed without taking measures to reduce errors (eg, independent study selection). A wide range of different tools was applied for critical appraisal. Moreover, the reporting of included economic evaluations and the synthesis of their results showed strong variations. Conclusions: Overall, we identified few common features in the applied methods for SR‐HEs. The information retrieval processes are largely standardized, but many studies did not use validated search filters. For the other systematic review steps, the methodological approaches varied. In particular, important challenges seem to be the methodological quality and transferability assessment as well as presentation and (quantitative) synthesis of results. Efforts are needed for increasing standardization, quality of applied methods, and reporting of SR‐HEs.